Artefacts and Living Artefacts. (1st November 2003) - Siipi, Helena
The concept of an artefact is central to several bioethical arguments. In this paper, I analyse this concept with respect to living and also non-living entities. It is shown that a close relationship between bringing an entity into existence and its intentional modification is necessary for its artefactuality. The criterion is further improved by analyses of the nature of intentionality in artefact production and the differences between artefacts and their side-effects. Further, in order to clarify the meaning of the term 'bring into existence', issues related to sortal terms and functions of artefacts are considered. As the result of these analyses, the criterion for being an artefact is founded on the following double condition: (1) An entity x is an artefact only if x has been intentionally brought into existence by intentionally causing the coming artefact x to have certain properties. (2) An entity x is an artefact only if causing x to have certain properties has led x to have some new functions - that is, functions that are not present in the raw materials of x. The double condition is used for clarifying the status of several biotic entities such as gardens, commercial fields, polluted natural areas, ecosystems including alien species, restored ecosystems and transgenic organisms.